2019
DOI: 10.1007/s40565-019-0563-0
|View full text |Cite
|
Sign up to set email alerts
|

Component importance assessment of power systems for improving resilience under wind storms

Abstract: Increasingly frequent natural disasters and manmade malicious attacks threaten the power systems. Improving the resilience has become an inevitable requirement for the development of power systems. The importance assessment of components is of significance for resilience improvement, since it plays a crucial role in strengthening grid structure, designing restoration strategy, and improving resource allocation efficiency for disaster prevention and mitigation. This paper proposes a component importance assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…It is necessary to quickly identify the contribution of each individual component to the overall reliability index. This paper adopts the reliability tracing method in [24]. It identifies the weak links that lead to the load curtailment risk and provides information for the decision-making of operators and planners.…”
Section: B Reliability Tracing Methodsmentioning
confidence: 99%
“…It is necessary to quickly identify the contribution of each individual component to the overall reliability index. This paper adopts the reliability tracing method in [24]. It identifies the weak links that lead to the load curtailment risk and provides information for the decision-making of operators and planners.…”
Section: B Reliability Tracing Methodsmentioning
confidence: 99%
“…It is demonstrated that criticality ranking is a useful tool for component intervention prioritisation in the preventive phase. In [69 ], a component importance assessment approach of power systems for improving resilience under windstorms is proposed based on Monte Carlo simulation.…”
Section: Enhancing Resiliencementioning
confidence: 99%
“…Reliability importance was first proposed by Birnbaum [16] in 1967, and has been widely used in production. Reliability importance refers to the degree to which the change of reliability of the component causes the change of system reliability, which is the change rate of system reliability to component reliability [7] . The formula is as follows: Because the machining center is a complex mechanical and electrical equipment, there is a close relationship between each component, any fault will affect the reliability of the whole machine, and also increase the maintenance cost.…”
Section: Linear Correlation Testmentioning
confidence: 99%
“…There are many disadvantages of the importance measurement base on the variance, the most obvious one is that the influence of different input variables on the output response may cancel each other [5] , the second is that in different stages, the importance of each components is different, and if only analyzing the importance of components in one stage will have many problems during the actual operation [6] , and as a complex mechanical and electrical equipment, the failure of a component may even cause the failure of the whole system, so during the process of reliability analysis of technical system, researchers usually find out the most sensitive components. Once the reliability of these components are improved, the reliability of the whole system can be improved, and finally the optimal solution model of the system can be obtained [7] .…”
Section: Introductionmentioning
confidence: 99%